The Effect Of Net Profit Margin (NPM), Price Earning Ratio (PER), And Earning Per Share (EPS) On Stock Prices In The Property And Real Estate Sector Listed On The Indonesia Stock Exchange For The Period 2015-2024 - Syawalia, Tasya; Fadli, Achmad Agus Yasin (Journal of Management, Economic, and Accounting, 2025)
This study aims to determine whether there is an influence between Net Profit Margin (NPM), Price Earning Ratio (PER), and Earning Per Share (EPS) partially and simultaneously on Stock Prices in the property and real estate sector in 2015-2024. This type of research is associative with quantitative methods using the SPSS version 25 application. Based on the results of the study, it was found that partially (t test), the Net Profit Margin (NPM) variable with Thitung -4.080 < 2.028 Ttable with a significance level of 0 < 0.05 indicates that Net Profit Margin (NPM) has a significant effect on Stock Prices. At the Price Earning Ratio (PER) with Thitung 2,143> 2,028 Ttable with a significance level of 0 < 0.05 indicates that the Price Earning Ratio (PER) has a significant effect on Stock Prices. Meanwhile, Earning Per Share (EPS) with Thitung 4,325> 2,028 Ttable with a significance level of 0 < 0.05 indicates that Earning Per Share (EPS) has a significant effect on Stock Price. Based on the results of the simultaneous significance test (F test), the results obtained Fcount 8.986> Ftable 2.87 with a significance level of 0 <0.05 that Net Profit Margin (NPM), Price Earning Ratio (PER), and Earning Per Share (EPS) together have a significant effect on stock prices in property and real estate sector companies listed on the Indonesia Stock Exchange for the period 2015-2024.